Women's knowledge, attitude, and practice of breast self- examination in sub-Saharan Africa: a scoping review - Roseline H. Udoh; Mohammed Tahiru; Monica Ansu-Mensah; Vitalis Bawontuo; Frederick Inkum Danquah; Desmond Kuupiel (BMC, 2020)
Abstract Background Breast cancer (BC) is a non-communicable disease with increased morbidity and mortality. Early detection of BC contributes to prompt linkage to care and reduction of complications associated with BC. Breast self-examination (BSE) is useful for detecting breast abnormalities particularly in settings with poor access to healthcare for clinical breast examination and mammography. Therefore, we mapped evidence on women's knowledge, attitude, and practice of BSE in sub-Sahara Africa (SSA). Methods We conducted a systematic scoping review using Arskey and O'Malleys' framework as a guide. We searched PubMed, Google Scholar, CINAHL, and Science Direct databases for relevant studies on women's knowledge, attitude and practice on BSE. Studies included in the review were from SSA countries as defined by the World Health Organization published from 2008 to May 2019. Two reviewers independently screened the articles at the abstract and full-text screening guided by inclusion and exclusion criteria. All relevant data were extracted, and a thematic analysis conducted. The themes were collated, and a narrative summary of the findings reported. Results Of the 264 potentially eligible articles identified from 595,144, only 21 met the inclusion criteria and were included for data extraction. These included studies were conducted in 7 countries of which 11 were conducted in Nigeria; two each in Ethiopia, Ghana, Cameroon, and Uganda; and one each in Kenya and Sudan. Of the 21 included studies, 18 studies reported evidence on BSE knowledge and practice; two on only knowledge; one on only practice only; and six presented evidence on women's attitude towards BSE. The study findings suggest varying knowledge levels on BSE among women in SSA countries. The study findings also suggest that BSE practice is still a challenge in SSA. Conclusion There is a paucity of published literature on women's knowledge, practice, and attitude of BSE in SSA. Hence, this study recommends further studies on knowledge, practice, and attitude of BSE, to identify contextual challenges and provide evidence-based solutions to improve women's knowledge, practice, and attitude of BSE in SSA.